Zonal shear layer collapse and the power scaling of the density limit: old L-H wine in new bottles. (1st August 2022) - Singh, Rameswar; Diamond, P H
Abstract: Edge shear layer collapse causes edge cooling and aggravates radiative effects. This paper details on the microscopic dynamics of the emergence of power ( Q ) scaling of density limit (DL) from the shear layer collapse transport bifurcation scenario. The analysis is based on a novel 4-field model, which evolves turbulence energy, zonal flow energy, temperature gradient and density, including the neoclassical screening of zonal flow response. Bifurcation analysis yields power scaling of critical density for shear layer collapse as n c r i t ∼ Q 1 / 3 . The favorable Q scaling of the DL emerges from the fact that the shear layer strength increases with Q, thus preventing shear layer collapse. This in turn reduces particle transport and improves particle confinement. RMP induced ambient stochastic fields degrade the shear layer by inducing decoherence in the Reynolds stress. As a result the particle transport increases and particle confinement degrades. This leads to the emergence of unfavorable stochastic field intensity ( b s t 2 ) scaling of the critical density as n c r i t ∼ ( 1 + b s t 2 ) − 5 / 3 . All fields, including zonal flow shear, exhibit hysteresis when the power ( Q ) is ramped cyclically across the bifurcation point. The hysteresis is due to dynamical delay in bifurcation on account of critical slowing down. Thus, the dynamical hysteresis here is fundamentally different from the hysteresis associated with the existence of bi-stable states.